Postnatal Morphometrical and Micrometrical development of liver gall bladder and Pancreas in Guinea Pig (Cavia porcellus) - Rajathi, S.; Ramesh, Geetah; Kannan, T.A.; Raja, K.; Paramasivan, S. (Indian Journal of Veterinary Anatomy, 2023)
The present research work was carried out to study the morphometry and micrometry of the liver, gall bladder and pancreas in postnatal age groups of guinea pig. Guinea pigs were procured from the Department of Laboratory Animal Medicine, Madhavaram Milk Colony, TANUVAS. After careful dissection of the animals, hepatopancreatic organ namely liver, gall bladder and pancreas were dissected out and morphometrical measurements namely length, width, thickness, weight and volume of the liver, gall bladder and pancreas were recorded in all the postnatal age groups. After routine histological procedures, micrometrical parameters of the liver, gall bladder and pancreas were also recorded.